Silver-tungsten high-entropy alloy electric contact material and preparation method thereof
Patent Information
- Application Number
- CN202611502041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
现有技术中,电接触材料表面花纹通常通过后续机械加工、激光刻蚀或模具压制获得,不仅增加了工序和成本,而且花纹与材料基体之间容易产生应力集中或结合不良
[0018]本发明的有益效果,本发明以含钨高熵合金骨架替代纯钨骨架,骨架由多主元合金形成,各主元元素在熔点与扩散行为上存在差异,骨架在烧结过程中的表面能与固溶体晶格畸变行为区别于纯钨,颗粒之间的孔隙尺寸分布较为集中且相互连通,银相能够在骨架中形成连续的网状分布,材料的微观组织均匀致密,闭孔与孔洞缺陷减少;多主元骨架的高温力学性能优于纯钨骨架,在电弧反复作用下骨架的坍塌和致密化烧结进程减缓,银相被挤出和汽化的进程随之延缓,触点的电寿命延长;同时,熔渗时银液经石墨板上表面的花纹凹槽分配并渗入骨架孔隙,花纹在熔渗过程中直接复制到材料表面,使带花纹的电接触材料能够一体成形,无需后续机械加工或激光刻蚀。
Smart Images

Figure CN123005202A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrical contact materials technology, specifically to a silver-tungsten high-entropy alloy electrical contact material and its preparation method. Background Technology
[0002] Silver-tungsten (AgW) electrical contact materials combine the excellent electrical and thermal conductivity of silver with the high hardness, arc erosion resistance, and anti-welding properties of tungsten, making them core functional materials for withstanding strong electric arcs in low-voltage circuit breakers and high-voltage switches. Currently, the mainstream industrial method for preparing silver-tungsten electrical contact materials is the melt infiltration method: tungsten powder is first pressed into a porous framework, which is then pre-sintered at high temperature to give the framework strength. Silver sheets are then placed on top of the framework and heated above the melting point of silver. Capillary action allows the molten silver to infiltrate into the pores of the framework, resulting in a dense silver-tungsten composite material.
[0003] The core control challenge of the melt infiltration method lies in the uniformity of the framework's pore structure and the wettability of the silver melt on the framework. In the silver-tungsten system, tungsten and silver are immiscible, and the wetting angle of the silver melt on the tungsten framework is as high as about 69° near the melting point. This leads to incomplete silver filling, leaving closed-pore defects in the material, and making it difficult to stably control the uniformity of silver distribution. To improve wettability, existing technologies typically add trace amounts of activating elements such as nickel, cobalt, and copper to the tungsten powder. Studies have shown that trace amounts of nickel and copper can reduce the wetting angle of the silver-tungsten system from 69° to 10° to 20°.
[0004] The above-mentioned approach has the following shortcomings. First, the trace additives are mostly low-melting-point metals, which are prone to selective segregation and excessive diffusion at high melting and infiltration temperatures, forming localized enrichment areas. This results in uneven wetting and a deviation of the silver phase distribution from the design, making it difficult to stably control the uniformity of the material structure. Second, the pure tungsten skeleton undergoes high-temperature densification sintering during repeated arc thermal cycling. The shrinkage of the skeleton volume causes the silver phase to be squeezed out of the contact surface, accelerating material failure and reducing the contact's electrical life.
[0005] Furthermore, in certain applications, electrical contact materials require specific patterns on their surfaces to improve arc-extinguishing performance, increase contact area, or serve as product identification. In existing technologies, surface patterns on electrical contact materials are typically obtained through subsequent machining, laser etching, or mold pressing. This not only increases the number of processes and costs but also makes it easy for stress concentration or poor bonding to occur between the pattern and the material substrate. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a silver-tungsten high-entropy alloy electrical contact material and its preparation method, which enables the silver phase to be continuously filled in the skeleton, resulting in a uniform and dense structure, slowing down the densification sintering of the skeleton under electric arc thermal cycling, extending the electrical life of the contact, and making the surface pattern integrally formed with the material body.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A silver-tungsten high-entropy alloy electrical contact material, comprising: Silver-tungsten high-entropy alloy framework; The silver phase continuously fills the pores of the silver-tungsten high-entropy alloy skeleton.
[0008] In this invention, a tungsten-containing high-entropy alloy refers to a multi-principal-element alloy composed of W, Ta, Nb, and M, wherein W is the principal element and M is one or more of Mo, Cr, and V. By mass percentage, the tungsten-containing high-entropy alloy contains 45%–65% W, 25%–30% Ta and Nb, and 10%–25% M, with the sum of the mass percentages of all elements being 100%. The high-entropy alloy referred to in this invention refers to the aforementioned multi-principal-element alloy, and its meaning is based on the above definition, without being further defined by the number of principal elements or the value of the mixed entropy.
[0009] As a further improvement of the present invention, the material of the silver-tungsten high-entropy alloy skeleton includes a tungsten-containing high-entropy alloy, which is composed of W, Ta, Nb and M, wherein M is one or more of Mo, Cr and V; by mass percentage, W in the tungsten-containing high-entropy alloy is 45%~65%, the total amount of Ta and Nb is 25%~30%, the total amount of M is 10%~25%, and the sum of the mass percentages of each element is 100%.
[0010] As a further improvement of the present invention, the surface of the silver-tungsten high-entropy alloy electrical contact material is provided with a pattern, the pattern being in the form of a grid, a dot matrix, or a groove, the depth of the pattern being 0.3~0.5 mm, the width or diameter being 0.8~1.2 mm, and the spacing being 1.5~2.5 mm.
[0011] A method for preparing a silver-tungsten high-entropy alloy electrical contact material is also provided, comprising the following steps: (1) Provide tungsten-containing high-entropy alloy powder and silver powder; (2) The tungsten-containing high-entropy alloy powder is subjected to Cu or Ni pre-plating treatment to obtain pre-plated powder, and the pre-plated powder is mixed with the silver powder to obtain mixed powder; (3) The mixed powder is pressed into shape to obtain a preform; (4) The preform is pre-sintered to obtain a silver-tungsten high-entropy alloy skeleton; (5) Graphite plates, pure silver sheets and the silver-tungsten high-entropy alloy skeleton are stacked sequentially from bottom to top, with the pure silver sheet located between the graphite plates and the silver-tungsten high-entropy alloy skeleton. Two-stage pressure insulation melting and infiltration are performed so that the molten silver liquid seeps into the pores of the silver-tungsten high-entropy alloy skeleton through the graphite plates, to obtain a silver-phase continuously filled silver-tungsten high-entropy alloy electrical contact material.
[0012] As a further improvement of the present invention, in step (1), the tungsten-containing high-entropy alloy powder is composed of W, Ta, Nb and M, where M is one or more of Mo, Cr and V; by mass percentage, W in the tungsten-containing high-entropy alloy powder is 45%~65%, the total amount of Ta and Nb is 25%~30%, the total amount of M is 10%~25%, and the sum of the mass percentages of each element is 100%; the average particle size of the tungsten-containing high-entropy alloy powder is 15~30 μm, and the average particle size of the silver powder is 5~20 μm.
[0013] As a further improvement of the present invention, in step (2), the thickness of the pre-plating layer in the pre-plating treatment is 0.1~0.5 μm, and the pre-plating method is chemical plating, electroplating or magnetron sputtering; the mixing adopts V-type mixing or three-dimensional mixing, and the mixing time is 4~8h.
[0014] As a further improvement of the present invention, in step (3), the pressing pressure is 200~400 MPa and the holding time is 1~3 min; in step (4), the pre-sintering is carried out in a vacuum or inert atmosphere, the pre-sintering temperature is 880~920℃, the holding time is 1.5~3 h, and the heating rate is 8~15℃ / min.
[0015] As a further improvement of the present invention, in step (5), the two-stage pressurized heat preservation melting infiltration includes: the first stage is kept at 1010~1030℃ for 1~2 h; the second stage is heated to 1080~1110℃ and kept at 1.5~2.5 h, while applying argon pressure of 0.2~0.8MPa.
[0016] As a further improvement of the present invention, in step (5), the thickness of the pure silver sheet is 0.5~2 mm, and the total amount of silver powder and the pure silver sheet is such that the mass fraction of silver in the silver-tungsten high-entropy alloy electrical contact material is 30%~41.7%.
[0017] As a further improvement of the present invention, in step (5), the upper surface of the graphite plate is provided with patterned grooves, which are in the form of a grid, a dot matrix, or a groove. The depth of the patterned grooves is 0.3~0.5 mm, the width or diameter is 0.8~1.2 mm, and the spacing is 1.5~2.5 mm. The patterned grooves form a silver liquid channel and replicate the pattern onto the surface of the silver-tungsten high-entropy alloy electrical contact material.
[0018] The beneficial effects of this invention are as follows: This invention uses a tungsten-containing high-entropy alloy skeleton instead of a pure tungsten skeleton. The skeleton is formed by a multi-principal element alloy, and the main elements have differences in melting point and diffusion behavior. The surface energy and solid solution lattice distortion behavior of the skeleton during sintering are different from those of pure tungsten. The pore size distribution between particles is more concentrated and interconnected, and the silver phase can form a continuous network distribution in the skeleton. The microstructure of the material is uniform and dense, and closed pores and void defects are reduced. The high-temperature mechanical properties of the multi-principal element skeleton are better than those of the pure tungsten skeleton. Under the repeated action of the electric arc, the collapse and densification sintering process of the skeleton is slowed down, and the process of silver phase being squeezed out and vaporized is delayed, thus extending the electrical life of the contacts. At the same time, during melting and infiltration, the silver liquid is distributed through the patterned grooves on the surface of the graphite plate and infiltrates into the pores of the skeleton. The pattern is directly replicated to the surface of the material during melting and infiltration, so that the patterned electrical contact material can be integrally formed without subsequent machining or laser etching. Attached Figure Description
[0019] Figure 1 The image shows a metallographic photograph of the silver-tungsten high-entropy alloy electrical contact material prepared in Example 1 of this invention. Figure 2 This is a conventional AgW electrical contact material prepared as Comparative Example 1 of the present invention. Detailed Implementation
[0020] The present invention will now be described in further detail with reference to the embodiments shown in the accompanying drawings.
[0021] This embodiment of a silver-tungsten high-entropy alloy electrical contact material includes: Silver-tungsten high-entropy alloy framework; The silver phase continuously fills the pores of the silver-tungsten high-entropy alloy skeleton.
[0022] The silver-tungsten high-entropy alloy framework forms a continuous load-bearing skeleton for the material. The silver phase fills the pores of the framework, creating interconnected conductive pathways between the framework particles. The framework is formed by a multi-principal element alloy, with each principal element exhibiting differences in melting point and diffusion behavior. Surface diffusion and neck growth of the framework particles during sintering are limited by solid solution lattice distortion, resulting in a relatively concentrated pore size distribution and high connectivity between pores. During melting and infiltration, molten silver can enter the framework stepwise along the interconnected pores under capillary action, forming a continuous network distribution within the framework. Once the silver phase is continuous, current is transmitted through the silver network, and heat generated by the electric arc can diffuse to the surrounding area through the silver network. The framework withstands the mechanical and thermal shocks of the electric arc, creating a mutually supportive relationship between the framework and the silver phase. This solves the problems of insufficient silver filling, discontinuous silver phase distribution, and insufficient microstructure uniformity caused by closed-pore residues in existing silver-tungsten electrical contact materials.
[0023] Further optimization can be achieved by selecting the following method: the material of the silver-tungsten high-entropy alloy skeleton includes a tungsten-containing high-entropy alloy, which is composed of W, Ta, Nb and M, where M is one or more of Mo, Cr and V; by mass percentage, W in the tungsten-containing high-entropy alloy is 45%~65%, the total amount of Ta and Nb is 25%~30%, the total amount of M is 10%~25%, and the sum of the mass percentages of each element is 100%.
[0024] W is the main element, providing a high-melting-point matrix resistant to arc erosion, allowing the framework to remain solid without collapsing at melting temperatures. Ta and Nb, with melting points higher than silver, also remain solid during melting, forming the high-temperature backbone of the framework together with W. Mo, Cr, and V, along with Ta and Nb, constitute a multi-principal element system. The substitution of these principal elements within the crystal lattice leads to lattice distortion, reducing the driving force for atomic diffusion and thus slowing the densification process during arc thermal cycling. Solid solution between the multi-principal elements lowers the system's free energy, and the formation of sintering necks between framework particles differs from that of a pure tungsten framework. Pores are uniformly distributed along the particle boundaries, reducing the likelihood of large or closed pores. This solves the problems of uneven porosity during melting infiltration and the rapid densification of the framework under arc thermal cycling, which can cause the silver phase to be squeezed out.
[0025] In order to obtain patterns directly on the material surface, in one alternative, the surface of the silver-tungsten high-entropy alloy electrical contact material is patterned, with the patterns being grid-like, dot-matrix-like, or groove-like, the depth of the patterns being 0.3~0.5 mm, the width or diameter being 0.8~1.2 mm, and the spacing being 1.5~2.5 mm.
[0026] The pattern is directly replicated from the grooves on the graphite plate surface during the melting and infiltration process. There is no processing interface between the pattern and the material body, resulting in a strong bond without stress concentration at the interface. The depth, width, or diameter, along with the spacing, are coordinated to create a regular undulation on the material surface: grid-like and grooved patterns form continuous grooves along the material surface, while dot-matrix patterns form discrete depressions. As the electric arc moves across the material surface, it is divided by the edges of the grooves, shortening the arc's dwell time at a certain position and improving arc extinguishing capability. The uniformly distributed grooves also ensure that the actual contact area between the material and the mating contacts is distributed according to the design value, resulting in more stable contact resistance. Compared to methods that rely on subsequent machining or laser etching to form patterns, this solution eliminates the corresponding processing steps and avoids stress concentration and poor bonding that easily occur at the processing interface. This solves the problems of existing methods for obtaining surface patterns in electrical contact materials, such as multiple processes, high costs, and poor bonding between the pattern and the substrate.
[0027] To achieve the industrial-scale preparation of the above materials, a method for preparing a silver-tungsten high-entropy alloy electrical contact material is further provided, comprising the following steps: (1) Provide tungsten-containing high-entropy alloy powder and silver powder; (2) The tungsten-containing high-entropy alloy powder is pre-plated with Cu or Ni to obtain pre-plated powder, and the pre-plated powder is mixed with silver powder to obtain mixed powder; (3) Press the mixed powder into shape to obtain a preform; (4) The preform is pre-sintered to obtain a silver-tungsten high-entropy alloy skeleton; (5) Graphite plates, pure silver sheets and silver-tungsten high-entropy alloy skeletons are stacked from bottom to top, with the pure silver sheets located between the graphite plates and the silver-tungsten high-entropy alloy skeletons. Two-stage pressure insulation melting and infiltration are carried out so that the molten silver liquid infiltrates into the pores of the silver-tungsten high-entropy alloy skeleton through the graphite plates, and a silver-phase continuously filled silver-tungsten high-entropy alloy electrical contact material is obtained.
[0028] Step (1) Use tungsten-containing high-entropy alloy powder instead of pure tungsten powder as the skeleton material. Prepare the powder and silver powder separately according to the proportion. Step (2) First, pre-plate the tungsten-containing high-entropy alloy powder with Cu or Ni so that the activation elements are attached to the powder surface in the form of a coating. Then mix the pre-plated powder with the silver powder. Since the activation elements exist in the form of a coating, their distribution on the powder surface is determined by the plating process rather than by the random dispersion during the mixing process. Therefore, the total amount of activation elements is small and the distribution is relatively uniform. It is not easy to form local enrichment areas in the subsequent high-temperature melting and infiltration. Step (3) Put the mixed powder into a mold and press it into shape. Under the action of pressure, the powder particles approach each other and interlock. There are interconnected pores between the powder particles, resulting in a preform with a certain shape and strength.
[0029] Step (4) involves pre-sintering the preform at a temperature lower than the melting point of silver but close to the sintering initiation temperature of the tungsten-containing high-entropy alloy powder. This allows the powder particles to form sintering necks and achieve the necessary bonding strength. The mixed silver powder remains solid at the pre-sintering temperature, and the pore network remains connected during the pre-sintering process, resulting in a porous silver-tungsten high-entropy alloy skeleton with silver particles distributed within the tungsten-containing high-entropy alloy matrix. In step (5), a graphite plate is placed at the bottom layer and serves as a support for the stacked assembly. Pure silver sheets are placed flat on the upper surface of the graphite plate, and the silver-tungsten high-entropy alloy skeleton is placed on top of the pure silver sheets. The three are stacked sequentially from bottom to top. After heating, the melted silver sheet spreads on the upper surface of the graphite plate and then, under the pressure of argon gas, penetrates into the pores of the silver-tungsten high-entropy alloy skeleton. When the upper surface of the graphite plate has a patterned groove, the silver liquid is also distributed horizontally along the groove, resulting in a more uniform distribution of the silver liquid below the skeleton. The first stage of heat treatment allows the molten silver to fully melt and spread on the graphite plate surface. The second stage involves continued heat treatment at an even higher temperature with argon pressure applied. Driven by this pressure, the molten silver overcomes the wetting resistance between itself and the framework, gradually expelling gas from the framework pores and filling them. After melting and infiltration, the furnace cools, and the molten silver solidifies within the framework pores, resulting in a silver-tungsten high-entropy alloy electrical contact material with continuous silver phase filling. This solves the problems of high-temperature segregation of activating elements when improving wettability through trace additives in existing melting and infiltration methods, and incomplete filling when the molten silver relies solely on capillary action.
[0030] In order to clarify the composition of the skeleton material and control the pore size in the compact, in one optional scheme, in step (1), the tungsten-containing high-entropy alloy powder is composed of W, Ta, Nb and M, where M is one or more of Mo, Cr and V; by mass percentage, W in the tungsten-containing high-entropy alloy powder is 45%~65%, the total amount of Ta and Nb is 25%~30%, the total amount of M is 10%~25%, and the sum of the mass percentages of each element is 100%; the average particle size of the tungsten-containing high-entropy alloy powder is 15~30 μm, and the average particle size of the silver powder is 5~20 μm.
[0031] The main components of the tungsten-containing high-entropy alloy powder are formulated according to the above proportions. During mechanical alloying or gas atomization, the powder forms a solid solution with W as the main component. The atoms of each main component occupy lattice positions in the solid solution, resulting in lattice distortion. The diffusion rate of atoms in the framework decreases, and the structural stability of the framework is correspondingly improved during arc thermal cycling. The lower limit of the W proportion enables the framework to resist arc erosion, while the upper limit of the W proportion enables the powder to form continuous sintering necks at the pre-sintering temperature without causing sintering difficulties. The total amount of Ta and Nb is controlled within this range to ensure that the framework maintains the necessary solid phase support at the melting and infiltration temperature. The average particle size of the powder determines the equivalent pore size between the pores after pressing: if the particle size is too large, the pore size is too large, and the silver liquid is prone to forming channels locally, resulting in uneven filling. At the same time, the contact points between framework particles are reduced, and the framework strength decreases. If the particle size is too small, the pore size is too small, and the resistance to be overcome when the silver liquid penetrates is increased. The average particle size of the silver powder is matched with that of the tungsten-containing high-entropy alloy powder, allowing the silver powder to fill the gaps between the tungsten-containing high-entropy alloy powder during mixing. After pressing, the silver powder is more evenly distributed in the blank, and the molten silver can replenish adjacent pores during melting and infiltration. The tungsten-containing high-entropy alloy powder can be prepared by mechanical alloying or gas atomization, and the average particle size can be determined by laser particle size analysis. This solves the problems of the skeleton easily collapsing at the melting and infiltration temperature when the skeleton composition is not properly designed, and the uneven infiltration of molten silver when the powder particle size and pore size do not match.
[0032] In order to improve the wettability of silver solution to the skeleton and suppress the segregation of active elements, in a specific scheme, in step (2), the thickness of the pre-plating layer is 0.1~0.5 μm, and the pre-plating method is chemical plating, electroplating or magnetron sputtering; the mixing adopts V-type mixing or three-dimensional mixing, and the mixing time is 4~8 h.
[0033] The pre-plating layer is formed as a continuous thin layer on the surface of tungsten-containing high-entropy alloy powder by plating. The thickness of the pre-plating layer is controlled within this range, so that the powder surface obtains an activation layer sufficient to reduce the wetting resistance of the silver liquid. At the same time, the total content of the activation elements in the skeleton is kept at a low level, so as not to form local enrichment areas at the high temperature of melting and infiltration. Chemical plating relies on reduction reaction to deposit the coating on the powder surface, which is suitable for powders with irregular shapes; electroplating relies on an external electric field to deposit the coating on the surface of conductive powder; magnetron sputtering relies on ion bombardment of the target to deposit the coating on the powder surface, and the coating has high purity and uniform thickness. All three of the above pre-plating methods can be implemented using conventional process conditions in this field. Mixing adopts V-type mixing or three-dimensional mixing to achieve uniform dispersion of pre-plated powder and silver powder under low mechanical shear. The mixing time is controlled within this range to ensure that the silver powder is evenly distributed in the billet and the powder does not undergo significant deformation. This can solve the problems of uncontrolled distribution of activation elements and selective agglomeration at the high temperature of melting and infiltration when improving wettability by adding trace additives.
[0034] In order to ensure that the preform has both strength and pore connectivity and that the pore network remains connected while maintaining the strength of the skeleton, in one optional scheme, in step (3), the pressing pressure is 200~400 MPa and the holding time is 1~3 min; in step (4), the pre-sintering is carried out in a vacuum or inert atmosphere, the pre-sintering temperature is 880~920℃, the holding time is 1.5~3 h, and the heating rate is 8~15℃ / min.
[0035] When the pressure is within this range, sufficient mechanical interlocking and contact are formed between the powder particles, and the billet possesses the strength required for transfer and furnace loading, while still retaining interconnected pore channels between the particles. Below this pressure range, the billet strength is insufficient, making it prone to breakage before pre-sintering and collapse during melting and infiltration; above this pressure range, the particles undergo significant plastic deformation, the pores are compressed or even closed, making it difficult for molten silver to penetrate. Holding time allows the pressure to be fully transmitted within the billet, resulting in a more uniform density throughout the billet. The pre-sintering temperature is below the melting point of silver but falls within the sintering initiation range of tungsten-containing high-entropy alloy powder. Sintering necks are formed between the powder particles, achieving the necessary connection strength, while the pore network does not close due to excessive shrinkage; below this pre-sintering temperature, the skeletal strength is insufficient; above this temperature, pore shrinkage is significant, connectivity decreases, and the incorporated silver powder tends to grow significantly. The heating rate is controlled within a relatively slow range to ensure that the internal and surface temperatures of the green body are consistent, preventing cracking caused by excessive internal and external temperature differences. A vacuum or inert atmosphere suppresses powder oxidation, allowing for the smooth formation of sintering necks between particles. The pressing and pre-sintering processes are interconnected; the interconnected pores formed during pressing provide pathways for neck growth during pre-sintering, while the skeletal strength formed during pre-sintering prevents the pores from collapsing under the subsequent high temperatures of melting and infiltration. This solves the problem of insufficient green body strength and closed pores caused by improper selection of pressing pressure and pre-sintering degree, which in turn affects the full infiltration of subsequent silver liquid.
[0036] In order to make the silver liquid filling more complete, in a specific scheme, the two-stage pressure heat preservation melting infiltration in step (5) includes: the first stage is kept at 1010~1030℃ for 1~2 h; the second stage is heated to 1080~1110℃ and kept at 1.5~2.5 h, while applying argon pressure of 0.2~0.8 MPa.
[0037] The first stage is held at a temperature higher than the melting point of silver, causing the silver sheet to completely melt and spread across the surface of the graphite plate. Simultaneously, it is distributed horizontally along the grooved patterns, providing a continuous supply of molten silver to the underside of the framework. The holding time in the first stage allows the flow of molten silver to stabilize. The second stage is held at an even higher temperature, further improving the fluidity of the molten silver and reducing the wetting resistance between it and the framework. Simultaneously, argon gas pressure is applied, forcing the molten silver into the pores of the framework. Gas in the pores is gradually expelled, and the molten silver fills the tiny pores that are difficult to penetrate by capillary action alone. Argon gas is chemically stable at the melting temperature and does not react with the molten silver or the framework. At this pressure range, it effectively drives the filling of the molten silver without causing it to overflow from the edges of the stacked components.
[0038] In order to balance the conductivity and resistance to arc erosion of the material, in step (5), the thickness of the pure silver sheet is 0.5~2 mm, and the total amount of silver powder and pure silver sheet makes the mass fraction of silver in the silver-tungsten high-entropy alloy electrical contact material 30%~41.7%.
[0039] Silver powder and pure silver sheets together constitute the silver source in the material. During the pressing stage, the silver powder is mixed with tungsten-containing high-entropy alloy powder and distributed within the blank. The pure silver sheets provide supplementary molten silver during the melting and infiltration stage. The mass fraction of silver is controlled within a certain range to ensure both a continuous conductive network within the material and sufficient skeletal volume to withstand the effects of electric arcs. If the silver mass fraction is too low, the silver network is discontinuous, the conductive path is too narrow, and localized temperature rise is excessively high under the influence of electric arcs. If the silver mass fraction is too high, the volume ratio of the skeletal structure decreases, reducing the material's hardness and resistance to arc erosion. The thickness of the pure silver sheet is coordinated with the silver mass fraction. If the pure silver sheet is too thin, the amount of supplementary silver provided in a single melting and infiltration is insufficient; if it is too thick, the height of the stacked components increases, leading to uneven distribution of molten silver. This solves the problems of discontinuous conductive paths due to insufficient silver content and decreased skeletal structure proportion due to excessive silver content.
[0040] In order to achieve the integral forming of the pattern and the material body, in a specific scheme, in step (5), the upper surface of the graphite plate is provided with patterned grooves. The patterned grooves are grid-like, dot-matrix-like or groove-like. The depth of the patterned grooves is 0.3~0.5mm, the width or diameter is 0.8~1.2mm, and the spacing is 1.5~2.5mm. The patterned grooves form a silver liquid channel and replicate the pattern to the surface of the silver-tungsten high-entropy alloy electrical contact material.
[0041] In this design, the grooved patterns on the upper surface of the graphite plate serve two functions. First, the grooves connect horizontally to form pathways. After the molten silver melts, it spreads and distributes along these grooves below the framework, then seeps upwards from the lower surface of the framework. The distribution of the molten silver below the framework is more uniform than when a pure silver sheet is laid flat. Second, the grooves form cavities during the melting and infiltration process. The molten silver fills these grooves and, after solidification, bonds with the material body. After the graphite plate is removed, the material surface is covered with patterns corresponding to the grooves. The depth, width, or diameter and spacing of the grooves are controlled within this range, ensuring that the patterns on the material surface exhibit undulations with matching depth and spacing, without weakening the material thickness at the patterned areas due to excessive groove depth. The size of the pattern is determined by the size of the grooves, with each pattern on the material surface corresponding to a specific groove. This solves the problems of multiple processes, high costs, and poor bonding between the pattern and the substrate in traditional pattern-obtaining methods.
[0042] In a specific embodiment 1, tungsten-containing high-entropy alloy powder was prepared by mechanical alloying at mass percentages of W55, Mo15, Ta15, and Nb15, with an average particle size of 20 μm. The silver powder had an average particle size of 10 μm and a purity of not less than 99.9%. The tungsten-containing high-entropy alloy powder was subjected to chemical Cu plating, with a pre-plating layer thickness of 0.3 μm. 30 kg of the pre-plated tungsten-containing high-entropy alloy powder and 20 kg of silver powder were mixed in a V-type mixer for 6 h to obtain a mixed powder. The mixed powder was pressed and shaped at 300 MPa and held for 2 min to obtain a preform. The preform was heated to 900℃ at 10℃ / min and held for 2 h in a vacuum furnace, followed by furnace cooling to obtain a silver-tungsten high-entropy alloy skeleton. A patterned graphite plate, a pure silver sheet with a thickness of 1 mm and a mass of 30 g, and the silver-tungsten high-entropy alloy skeleton were stacked sequentially from bottom to top. The patterned graphite plate had a grid-like pattern depth of 0.5 mm. The material has a diameter of 1 mm, a width of 1 mm, and a spacing of 2 mm. It undergoes two-stage pressurized and heat-preserving melting infiltration in an argon atmosphere furnace. The first stage is held at 1020℃ for 1 h, and the second stage is heated to 1080℃ and held for 1.5 h while applying 0.5 MPa argon pressure. After melting infiltration, it is cooled to room temperature with the furnace to obtain a patterned silver-tungsten high-entropy alloy electrical contact material with continuous silver phase filling and a silver mass fraction of 40%.
[0043] In another specific embodiment 2, tungsten-containing high-entropy alloy powder was prepared according to the mass percentages of W45, Mo10, Ta15, Nb15, and Cr15, using a gas atomization method, with an average particle size of 30 μm; the silver powder had an average particle size of 20 μm; the tungsten-containing high-entropy alloy powder was subjected to magnetron sputtering Ni plating, with a pre-plating layer thickness of 0.5 μm; 35 kg of the pre-plated tungsten-containing high-entropy alloy powder and 25 kg of silver powder were mixed in a three-dimensional mixer for 8 h to obtain a mixed powder; the mixed powder was pressed and shaped at 400 MPa and held for 3 min to obtain a preform; the preform was heated to 920℃ at 8℃ / min and held for 3 h in an argon atmosphere to obtain a silver-tungsten high-entropy alloy skeleton; the patterned graphite plate had a dot matrix pattern with a depth of 0.3 mm, a dot diameter of 0.8 mm, and a spacing of 1.5 mm; the pure silver sheet had a thickness of 2 mm and a mass of 35 g; the first section was held at 1010℃ for 2 h. h, the second stage is heated to 1110℃ and held for 2 h with 0.8 MPa argon pressure applied; cooled with the furnace, a silver-tungsten high-entropy alloy electrical contact material with a dot matrix pattern is obtained, with a silver mass fraction of 41.7%.
[0044] In another specific embodiment 3, tungsten-containing high-entropy alloy powder was prepared by mechanical alloying according to the mass percentages of W65, Ta15, Nb10, and V10, with an average particle size of 15 μm; the silver powder had an average particle size of 5 μm; the tungsten-containing high-entropy alloy powder was electroplated with Cu, with a pre-plating layer thickness of 0.1 μm; 35 kg of the pre-plated tungsten-containing high-entropy alloy powder and 15 kg of silver powder were mixed in a V-type mixer for 4 h to obtain a mixed powder; the mixed powder was pressed and shaped at 200 MPa and held for 1 min to obtain a preform; the preform was heated to 880℃ at 15℃ / min under vacuum and held for 1.5 h to obtain a silver-tungsten high-entropy alloy skeleton; the patterned graphite plate had a grooved pattern with a groove depth of 0.4 mm, a groove width of 1.2 mm, and a groove spacing of 2.5 mm; the pure silver sheet had a thickness of 0.5 mm and a mass of 25 g; the first section was held at 1030℃ for 1 h. h, the second stage is heated to 1100℃ and held for 2.5 h with 0.2 MPa argon pressure applied; cooled with the furnace, a grooved silver-tungsten high-entropy alloy electrical contact material is obtained, with a silver mass fraction of 30%.
[0045] As a control, in Comparative Example 1, pure tungsten powder was used instead of tungsten-containing high-entropy alloy powder, and the pure tungsten powder was pre-plated with Cu or Ni. The average particle size of the pure tungsten powder was 20 μm, and the average particle size of the silver powder was 10 μm. 30 kg of the pre-plated pure tungsten powder and 20 kg of silver powder were mixed, pressed into shape at 300 MPa, and pre-sintered under vacuum at 900℃ for 2 h to obtain a pure tungsten skeleton. Patterned graphite plate, 30 g of pure silver sheet and pure tungsten skeleton were stacked from bottom to top, and the other conditions were the same as those in the first specific implementation above.
[0046] The performance comparison data obtained from testing the above-mentioned finished products are as follows: Performance comparison data
[0047] Data shows that the patterned silver-tungsten high-entropy alloy electrical contact materials prepared in Examples 1-3 of this invention, with silver contents of 40%, 50%, and 30%, respectively, exhibit higher density than Comparative Example 1 (pure tungsten skeleton), significantly improved hardness, markedly reduced mass loss due to arc erosion, and a substantial extended electrical life. Although the resistivity of Examples 1-3 is slightly higher than that of Comparative Example 1, it is still within the acceptable range for electrical contact materials, and their overall performance is superior. This indicates that replacing pure tungsten with a tungsten-containing high-entropy alloy as the skeleton material, combined with Cu or Ni pre-plating treatment and a two-stage pressure melting process, can effectively improve the wettability and filling continuity of the silver liquid, delay the densification sintering process of the skeleton under arc thermal cycling, thereby significantly improving the arc erosion resistance and electrical life of the electrical contact material.
[0048] Figure 1 The image shows a metallographic photograph of the silver-tungsten high-entropy alloy electrical contact material prepared in Example 1 of this invention. Figure 2 The image shows a metallographic photograph of the conventional AgW electrical contact material prepared in Comparative Example 1. As can be seen from the figure, the silver-tungsten high-entropy alloy electrical contact material prepared in Example 1 of this invention (…) Figure 1 The microstructure is uniform and dense, with the silver phase (light-colored area) distributed in a continuous network within the tungsten-containing high-entropy alloy framework (dark-colored area). The framework particles are fine and uniform, and no obvious defects such as closed pores, voids, or cracks were observed. In contrast, the traditional AgW electrical contact material prepared in Comparative Example 1 ( Figure 2 The microstructure is significantly uneven, the silver phase distribution is discontinuous, and there are pore aggregation areas and local segregation of skeletal particles. Compared with traditional AgW electrical contact materials, the material of this invention exhibits higher density, more uniform phase distribution and more continuous silver network in its microstructure.
[0049] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A silver-tungsten high-entropy alloy electrical contact material, characterized in that, include: Silver-tungsten high-entropy alloy framework; The silver phase continuously fills the pores of the silver-tungsten high-entropy alloy skeleton.
2. The silver-tungsten high-entropy alloy electrical contact material according to claim 1, characterized in that, The silver-tungsten high-entropy alloy framework is made of a tungsten-containing high-entropy alloy, which is composed of W, Ta, Nb and M, where M is one or more of Mo, Cr and V. By mass percentage, W in the tungsten-containing high-entropy alloy is 45% to 65%, the total amount of Ta and Nb is 25% to 30%, the total amount of M is 10% to 25%, and the sum of the mass percentages of each element is 100%.
3. The silver-tungsten high-entropy alloy electrical contact material according to claim 1, characterized in that, The surface of the silver-tungsten high-entropy alloy electrical contact material is patterned, and the pattern is in the form of a grid, dot matrix, or groove. The depth of the pattern is 0.3~0.5mm, the width or diameter is 0.8~1.2mm, and the spacing is 1.5~2.5mm.
4. A method for preparing a silver-tungsten high-entropy alloy electrical contact material, characterized in that, Includes the following steps: (1) Provide tungsten-containing high-entropy alloy powder and silver powder; (2) The tungsten-containing high-entropy alloy powder is subjected to Cu or Ni pre-plating treatment to obtain pre-plated powder, and the pre-plated powder is mixed with the silver powder to obtain mixed powder; (3) The mixed powder is pressed into shape to obtain a preform; (4) The preform is pre-sintered to obtain a silver-tungsten high-entropy alloy skeleton; (5) Graphite plates, pure silver sheets and the silver-tungsten high-entropy alloy skeleton are stacked sequentially from bottom to top, with the pure silver sheet located between the graphite plates and the silver-tungsten high-entropy alloy skeleton. Two-stage pressure insulation melting and infiltration are performed so that the molten silver liquid seeps into the pores of the silver-tungsten high-entropy alloy skeleton through the graphite plates, to obtain a silver-phase continuously filled silver-tungsten high-entropy alloy electrical contact material.
5. The method for preparing the silver-tungsten high-entropy alloy electrical contact material according to claim 4, characterized in that, In step (1), the tungsten-containing high-entropy alloy powder is composed of W, Ta, Nb and M, where M is one or more of Mo, Cr and V; by mass percentage, W in the tungsten-containing high-entropy alloy powder is 45%~65%, the total amount of Ta and Nb is 25%~30%, the total amount of M is 10%~25%, and the sum of the mass percentages of each element is 100%; the average particle size of the tungsten-containing high-entropy alloy powder is 15~30μm, and the average particle size of the silver powder is 5~20μm.
6. The method for preparing the silver-tungsten high-entropy alloy electrical contact material according to claim 4, characterized in that, In step (2), the thickness of the pre-plating layer in the pre-plating treatment is 0.1~0.5μm, and the pre-plating method is chemical plating, electroplating or magnetron sputtering; the mixing adopts V-type mixing or three-dimensional mixing, and the mixing time is 4~8h.
7. The method for preparing the silver-tungsten high-entropy alloy electrical contact material according to claim 4, characterized in that, In step (3), the pressing pressure is 200~400MPa and the holding time is 1~3min; in step (4), the pre-sintering is carried out in a vacuum or inert atmosphere, the pre-sintering temperature is 880~920℃, the holding time is 1.5~3h, and the heating rate is 8~15℃ / min.
8. The method for preparing the silver-tungsten high-entropy alloy electrical contact material according to claim 4, characterized in that, In step (5), the two-stage pressurized heat preservation melting infiltration includes: the first stage is kept at 1010~1030℃ for 1~2h; the second stage is heated to 1080~1110℃ and kept at 1.5~2.5h, while applying argon pressure of 0.2~0.8MPa.
9. The method for preparing the silver-tungsten high-entropy alloy electrical contact material according to claim 4, characterized in that, In step (5), the thickness of the pure silver sheet is 0.5~2mm, and the total amount of silver powder and pure silver sheet is such that the mass fraction of silver in the silver-tungsten high-entropy alloy electrical contact material is 30%~41.7%.
10. The method for preparing the silver-tungsten high-entropy alloy electrical contact material according to claim 4, characterized in that, In step (5), the upper surface of the graphite plate is provided with patterned grooves. The patterned grooves are in the form of a grid, a dot matrix, or a trench. The depth of the patterned grooves is 0.3~0.5mm, the width or diameter is 0.8~1.2mm, and the spacing is 1.5~2.5mm. The patterned grooves form a silver liquid channel and replicate the pattern onto the surface of the silver-tungsten high-entropy alloy electrical contact material.
